PEMBANGUNAN BERKELANJUTAN: DAMPAK PENGEMBANGAN APARTEMEN DI DAERAH SLEMAN TERHADAP KEHIDUPAN MASYARAKAT - Pasmaka Pindo Harahap (Inovasi Pembangunan : Jurnal Kelitbangan, 2020)
In this paper, I discuss the impact of the construction of Uttara The Icon Apartment in Sleman Regency, the relationship between the government, the private sector and the community, the role of the government in dealing with conflicts that occur in the building construction process, and their impact on the environment. This paper is based on a literature study that I did, and is also descriptive in explaining the problems in it. This paper aims to provide information to the reader regarding the case that occurred between the building management and also the community when the construction took place, as well as how big the role of the government and also the impact arising from the existence of this project. From the results of this study emerged various agrarian conflicts, ranging from water conflicts, the environment to social conflicts that occurred.